Prevalence of Trypanosoma cruzi Infection in Pregnant Women and Risk of Vertical Transmission in Newborns in Chiapas, Mexico - Sury Antonio López Cancino; Leticia Eligio García; María del Pilar Crisóstomo Vázquez; Mariana Soria Guerrero; Enedina Jiménez Cardoso; Marcos Meneses Mayo; Sergio Agustín Islas Andrade (Tropical Medicine and Infectious Disease)
The Mexican state of Chiapas is considered epidemiologically significant for Chagas disease due to the coexistence of infected reservoirs and vectors, including migratory populations from Central and South America. However, there is a lack of monitoring programs for the timely detection of this disease. The objective of this study was to elucidate the prevalence of Trypanosoma cruzi infection in pregnant women and the risk of vertical transmission in newborns at two hospitals located in the Metropolitan Region of Tuxtla Gutierrez, the capital of Chiapas State Mexico. A cross-sectional study was carried out with 193 pregnant women with gestational ages between 32 and 40 weeks, who underwent immunological testing to diagnose Chagas disease. Conventional PCR testing on cord blood revealed the presence of T. cruzi in newborns. The prevalence of T. cruzi infection in pregnant women was 32.12% (95% confidence interval (CI): 0.25, 0.38). The 62 pregnant women who tested positive for Chagas disease gave birth to 63 children, and in 5 newborns (8% (5/62), 95% confidence interval (CI): 0.02, 0.19), PCR tests on umbilical cord blood were positive for T. cruzi. In conclusion, the dataset showed a high prevalence of Chagas disease in the sample of pregnant women studied and a maternal–fetal transmission rate of 8%.